En Plein Air: Examining Child Art in Our Open Field - Smith, Victoria Ford (Journal of Juvenilia Studies)

(untitled) (International Society of Literary Juvenilia, 2026)
This essay is part of this issue's Editor's Column on the theme "Surveying Our Spacious Field." Scholars working on the cultural productions of children use a variety of disciplinary approaches and deploy a spectrum of terms to describe our practices: juvenilia studies, childhood studies, and studies of child-produced culture, for example. Rather than arguing for one approach or definition, this essay celebrates the openness of our field and reflects on benefits of applying diverse methodologies. As a case study, it explores four exhibits of child art that Stieglitz staged in his famous 291 gallery in New York City between 1912 and 1916, now held in the Alfred Stieglitz/Georgia O’Keeffe Archive at Yale University’s Beinecke Rare Book and Manuscript Library.